Development of experimental GBS vaccine for mucosal immunization. - T Gupalova; G Leontieva; T Kramskaya; K Grabovskaya; E Bormotova; D Korjevski; A Suvorov (PLoS ONE, 2018)
Streptococcus agalactiae, or group B streptococcus (GBS), is an important pathogen as it is the leading cause of neonatal deaths due to sepsis, meningitis or bacterial pneumonia. Although the development of an effective and safe GBS vaccine is on the agenda of many research labs, there is no GBS vaccine on the market yet. In the present study we attempted to engineer a live vaccine strain based on Bac, a surface protein of GBS, incorporated into a surface fimbrial protein of probiotic Enterococcus. The resulting strain induced specific systemic and local immune responses in mice and provided protection against GBS when administered via the intranasal, oral or intravaginal immunization routes.